Optimization of quantum trajectories driven by strong-field waveforms - Haessler,S; Balciunas,T; Fan,G; Andriukaitis,G; Pugzlys,A; Baltuska,A; Witting,T; Squibb,R; Zair,A; Tisch,JWG; Marangos,JP; Chipperfield,LE (Physical Review X, 2014)
Quasifree field-driven electron trajectories are a key element of strong-field dynamics. Upon recollision with the parent ion, the energy transferred from the field to the electron may be released as attosecond-duration extreme ultaviolet emission in the process of high-harmonic generation. The conventional sinusoidal driver fields set limitations on the maximum value of this energy transfer and the efficient return of the launched electron trajectories. It has been predicted that these limits can be significantly exceeded by an appropriately ramped-up cycle shape [L. E. Chipperfield et al., Phys. Rev. Lett. 102, 063003 (2009)]. Here, we present an experimental realization of similar cycle-shaped waveforms and demonstrate control of the high-harmonic generation process on the single-atom quantum level via attosecond steering of the electron trajectories. With our improved optical cycles, we boost the field ionization launching the electron trajectories, increase the subsequent field-to-electron energy transfer, and reduce the trajectory duration. We demonstrate, in realistic experimental conditions, 2 orders of magnitude enhancement of the generated extreme ultraviolet flux together with an increased spectral extension. This application, which is only one example of what can be achieved with cycle-shaped high-field light waves, has significant implications for attosecond spectroscopy and molecular self-probing.